Rejung as Cultural Resistance: Oral Tradition and Identity Transmission in the Semende Ethnic Tradition in South Sumatra, Indonesia - Hidayatullah, Fadhilah; Widodo, Widodo; Sugiarto, Eko; Machfauzia, Ayu Niza (Journal of Education Culture and Society, 2026)
Aim. This research aims to examine the paradigm of oral tradition transmission of the Rejung people in the Semende community through an ethnopedagogical perspective.Methods. The method used in this research is a qualitative research approach with an ethnographic orientation.Results. The research findings indicate that rejung, as an oral tradition of the Semende people, is not merely a form of expressive art, but also a manifestation of a living and continuously evolving local knowledge system. Through its poetic structure, mother tongue, and socio-communal context, the rejung plays a dual role as a medium of oral pedagogy and cultural articulation that is resistant to the dominance of formal and global epistemologies. Within a pedagogical framework, the rejung provides an alternative educational model that is contextual, participatory, and based on collective experience. The process of passing down the rejung through vertical (parent to child), horizontal (peer to peer), and oblique (traditional figure to community) channels reflects the strength of social relationships in the reproduction of values, ethics, and spirituality. The knowledge contained in the rejung is not conveyed instructionally, but rather through affective, performative, and symbolic engagement that is integrated into the daily lives of the community.Conclusion. Rejung serves as evidence that knowledge systems based on local experience, spirituality, and mother tongue have their own validity, no less meaningful than formal education systems. Therefore, recognising pedagogical practices like rejung is an important step in building inclusive, contextual, and epistemically just education.